Vladimir Zelinskij. BUDʹTE KAK DETI. TEOFANIJA DETSTVA - Golubovich, Inna (Bogoslovskie razmyšlenija, 2020)
BOOK REVIEW:Be like children. Theophany of childhood. Vladimir Zelinsky.M .: Nikea, 2019. 304 p. ISBN 978-5-91761-978-1; 550.00 RUBIn 2020, it suddenly turned out that the world order was incredibly fragile. Habit my life began to crumble like dominoes, "as she accurately described current situation of O.A.Sedakova. Nothing lasts longer and unshakable. There is an unprecedented violation of the established rhythm and lifestyle. The only ones least affected by this global laps are children. And looking at this unexpectedly opened inner invulnerability the most seemingly vulnerable want to re-read the book of famous Orthodox priest and theologian Vladimir Zelinsky "Be like children. Theophany of childhood."